COVID-19: Fear and Anxiety among Healthcare Workers in Saudi Arabia. A Cross-Sectional Study. (July 2021) - Mohsin, Syed Fareed; Agwan, Muhammad Atif; Shaikh, Sameer; Alsuwaydani, Ziyad Ahmad; AlSuwaydani, Saleh Ahmad
The novel coronavirus (COVID-19) is an extremely contagious respiratory disease. It poses a serious threat to healthcare workers which may cause substantial degree of psychological distress. This study aimed to evaluate the level of fear and anxiety among healthcare workers. A cross sectional study was designed to collect data from healthcare workers in Saudi Arabia using an online questionnaire. A non-probability convenient sampling technique was used to collect the data from 1st August to 10th August 2020 with the exclusion of non-healthcare worker and general public. A 5-point Likert scale was used to evaluate the level of fear and anxiety. The data was analyzed by using Spss version 23 .The descriptive data were represented as frequencies and percentage. Multinomial logistic regression analysis was applied to control the confounding factors and assess the relationship between variables. Data analyzed 737 participants revealed that 10.7%, 73.5%, and 15.7% of HCWs had a mild, moderate, and severe degree of fear and anxiety respectively. The multinomial logistic regression analysis revealed that gender and specialty of the participants were significantly associated with moderate and severe anxiety level. This study demonstrates that two-third of the healthcare workers had a moderate risk of fear and anxiety. However, females participants found to have elevated fear and anxiety level. Social distancing has a major impact on social well-being therefore its important to address social support through a policy. Further studies are needed to explore the mental health condition of healthcare workers in order to develop evidence based strategies.